Effect Of Single And Co-Doping Of Strontium And Silver On Properties Of Sol-Gel Derived Quaternary Bioactive Glass - Swe, Thet Thet (2021)
Bioactive glasses (BG) have been considered as one of the most promising materials for bone regeneration due to its property to bond with both soft and hard tissues and the capability to release ions overtime that have a positive effect on the bone cell proliferation and differentiation in-vitro and in-vivo. However, the bone regeneration in patient who suffer osteoporosis disease and the re-occurrence of bacterial infection limit its biomedical applications. BG can bond to hard tissue and degrades over time but the bone regeneration capacity of osteoporotic bones is generally slower than that of normal bones. Therefore it limits the application of BG. Also, bacterial infection is serious sometimes it needs to second surgery with a lot of suffering and there is still re-occurrence of bacterial infection after surgery. To overcome this limitation, the implant BG should possess long-term antibacterial property. However, these limitations could be overcome by doping of therapeutic ions into BG system. Hence, the purpose of this study is to dope strontium (Sr2+) and silver (Ag+) into quaternary silicate BG to enhance the in-vitro bioactivity (particularly bone formation for osteoporotic disease) and antibacterial properties (bacterial infection re-occurrence). This is performed by sol-gel method which include mixing, gelation, aging, drying and calcination. BG with S53P4 composition was used as a control and two new compositions (S50P4 and S55P4) was developed from SiO2-CaO-Na2O-P2O5 quaternary system. Strontium (Sr2+) is bone seeker trace elements which possess positive effects on bone formation (osteogenesis). Thus, the Sr2+ concentration of 1, 3 and 5 mol% was chosen and the compositions were categorized as BG-1S, BG-3S and BG-5S in this study. On the other hand, low concentration of Ag+ has an effect on bacterial infection and the concentration of 1, 2 and 3 mol% was chosen for silver doping and denoted as BG-1A, BG-2A and BG-3A accordingly. X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) revealed that the doping of Sr2+ and Ag+ did not change the silicate structure as well as combeite phase. The in-vitro bioactivity test soaking in Hank’s balanced salt solution (HBSS) for 3, 7 and 14 days confirmed on the hydroxyl-carbonated (HCA) formation on the specimens’ surface with emerging of HA peaks in XRD and the carbonated (C-O bond) and phosphate groups (P-O bond) in FTIR spectra. However, less intense apatite formation was observed in Ag doped BGs compared to Sr-doped BG while Sr-BG showed the enhanced in apatite formation after 14 days soaking in HBSS. The in-vitro biocompatibility test with MC3T3-E1 osteoblast like cells proved that 3 mol% of Sr2+ and 1 mol% of Ag+ observed the highest in both cells proliferation (cells viability) and Alkaline phosphatase (ALP) activity. Moreover, the mineralization staining for bone-like formation was improved after Sr2+ and Ag+ doped into glass formulation compared with undoped specimen (BG-0). Interestingly, the multi-doped (Sr and Ag) bioglass specimen (BG-3S1A) showed cytocompatibility which demonstrated the positive effect of the combination of Sr2+and Ag+ ions on MC3T3-E1 osteoblast cell proliferation as well as the staining areas for BG-3S1A are significantly higher than those of other specimens. Moreover, the bacterial response of multi-doped composition (BG-3S1A) had the comparable inhibition zone of Ag-BG against E.coli and S.aureus bacteria. Summarizing, the multi-doped combination of Sr2+ and Ag+ ion into bioactive glass was successfully developed by sol-gel method and exhibiting improved in-vitro biocompatibility and antibacterial properties.